Evaluation of Nutritional Status for Some Sensitive Sets and its Relationship to Natural Antioxidants - Rokayya A. Sami; Ebtihal Y. Khojah; Eman A. Elgarni; Nada Benajiba (Journal of King Abdulaziz University: Medical Sciences, 2023)
There exists a need to get the knowledge of natural antioxidants’ sources as a result of several factors; perhaps most notably is the change in our lifestyle. Although modern life has become easier and more comfortable, it harms us in diff erent ways. So, we should look for the best ways to support our health. Although our body manufactures antioxidants, we need additional quantities for protecting the body. Natural antioxidants are found in fresh vegetables, fruits, seafood and some nuts. Sport is essential for our health. The short period sports could increase the antioxidant production quickly too. Groups of children, adolescents, adults and elderly have been tested. A selfadministered questionnaire asking about socio-demographic data, various forms of activities, dietary intakes and habits was used for data collection. The elementary schoolchildren were interviewed by structured interview to gather information. Therefore, there is a necessity to develop a nutrition education program in order to change lifestyle habits and avoid the negative health consequences.